Pendampingan Pengembangan Usaha Produksi Roti di Husna Roti Desa Purwosari Kecamatan Comal Kabupaten Pemalang - Yayan Nuryana; Victor Prasetya; Nisrina Nisrina; Siti Intan Rahayu; Siti Nurarofah; Tiara Tirta Wulandari; Chafid Syukron (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Husna Roti is a business specializing in cakes and bakery products that has been operating for nine years in Desa Purwosari, Comal District, Pemalang Regency. As part of a community service program, faculty members and students are involved in providing assistance to help develop this business. The program includes various improvement efforts, particularly in the areas of marketing and human resource management. The actions taken include creating Grabfood and Instagram accounts to expand the digital market, making official stamps, obtaining halal certification, and producing promotional videos and documenting the production process. Additionally, the company profile and organizational structure were prepared to strengthen management. Financial reports and cost of goods sold calculations were also made to optimize cost management. Through this collaboration, the faculty members and students aim to provide concrete solutions to the challenges faced by Husna Roti. With this assistance, it is hoped that the quality of the products and the competitiveness in the market will improve, allowing the business to grow and positively impact the local economy.